Implementation of Full Day School Program Development in Student Character Development at Nurul Ilmi IT Junior High School - Juniani, Ella; Dora, Nuriza (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This research looks at how SMP IT Nurul Ilmi implements the Full Day School program to build student character. The need to improve the quality of students' character education by integrating a comprehensive program with daily teaching and learning activities is the basis of this research. The purpose of this study is to find out how well the Full Day School program helps students develop into religious, disciplined, and responsible individuals. Observation, interviews, and documentation are the methods used to collect data in a qualitative research approach. The research subjects were students, teachers, and the head of SMP IT Nurul Ilmi. The results showed that the Full day school program has a significant influence on students' character development. Discipline, responsibility, and religious attitude have improved among the students.